2007
DOI: 10.1111/j.1440-1827.2007.02149.x
|View full text |Cite
|
Sign up to set email alerts
|

Enteritis necroticans ‘pigbel’ in a Japanese diabetic adult

Abstract: Enteritis necroticans 'pigbel' is caused by Clostridium perfringens type C but has rarely been reported in developed countries. A 50-year-old Japanese man with untreated diabetes mellitus (DM) presented with diarrhea and abdominal pain. Intraoperative endoscopic and macroscopic examination disclosed segmental annular mucosal lesions characteristic of clostridial enteritis. Clostridial infection type C was verified on pathological, and immunohistochemical analysis. Although rare, the disease is likely to be und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
34
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 12 publications
(24 reference statements)
1
34
1
Order By: Relevance
“…Although less common, this disease also occurs in diabetic patients from developed countries. Persons suffering from enteritis necroticans often survive less than 48 h after the first appearance of symptoms (9,16,21,26). Histologically, the disease is characterized by necrotic enteritis and the presence of numerous bacteria in the intestinal lumen (29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although less common, this disease also occurs in diabetic patients from developed countries. Persons suffering from enteritis necroticans often survive less than 48 h after the first appearance of symptoms (9,16,21,26). Histologically, the disease is characterized by necrotic enteritis and the presence of numerous bacteria in the intestinal lumen (29).…”
mentioning
confidence: 99%
“…Histologically, the disease is characterized by necrotic enteritis and the presence of numerous bacteria in the intestinal lumen (29). Immunohistochemistry studies using anti-CPB antibodies showed the presence of CPB on the necrotic intestinal epithelium of humans suffering from type C infection (9).…”
mentioning
confidence: 99%
“…Today, this disease still occurs sporadically in malnourished people in many developing countries (17). EN cases also occur occasionally in developed countries, particularly in people with pancreatic disease (18,19).…”
mentioning
confidence: 99%
“…EN is characterized by its sudden onset with abdominal cramps, shock, bloody diarrhea, acute inflammation, and pronounced necrosis of intestinal mucosa (27,31). Necrosis of the intestinal epithelium always coincides with the presence of Gram-positive rods characteristic of C. perfringens attached to the surface of the necrotic mucosa that, when visualized by microscopy, appear to form biofilm-like structures (28,29). CPB, the most important toxin for developing EN (32)(33)(34), has been detected on the apical side of intestinal cells underneath those attached bacteria, indicating that in situ production of CPB is important for pathogenesis (29).…”
mentioning
confidence: 99%
“…perfringens type C is the etiologic agent of human enteritis necroticans (also called pigbel, darmbrand, or "gangrene of the bowel"), which originates in the intestine (2). Enteritis necroticans (EN) is particularly aggressive in diabetics and immunocompromised patients from developed countries (they survive less than 48 h after the first appearance of symptoms) (25)(26)(27)(28)(29)(30). EN is characterized by its sudden onset with abdominal cramps, shock, bloody diarrhea, acute inflammation, and pronounced necrosis of intestinal mucosa (27,31).…”
mentioning
confidence: 99%